Biopuncture the management of common orthopedic and sports disorders - Kersschot, Jan (Thieme, 2014)
Written by the creator of the biological injection technique, Biopuncture is a practical guide to the therapeutic use of biopuncture in treating musculoskeletal disorders. It provides detailed discussions of therapeutic strategies, contraindications, and expert advice on dealing with complications.